External influences on the roles of Lundayeh dance music in Tenom, Sabah - Maine Suadik; Yusten Karulus; Ricky Yakub Ganang; Bayre Suadik (Penerbit Universiti Malaysia Sabah, 2025)
Dance music has long been a fundamental aspect of Lundayeh's identity; however, external factors—such as tourism-driven commercialisation promoting cultural visibility—are increasingly shaping its role and meaning within the community. This study explores the impacts of these external forces on Lundayeh dance music, focusing on how its role and authenticity within the community are being redefined. Fieldwork was conducted across three villages in Tenom, Sabah—Kampung Sugiang Baru, Kampung Baru Jumpa, and Kampung Kalibatang Baru—where data were collected using qualitative methods, including in-depth interviews, focus group discussions, and observations with community members and cultural practitioners. The findings reveal a complex interaction between traditional values and contemporary influences, showing the adaptive resilience of Lundayeh dance music and the potential risks of cultural erosion. This research provides insight into the broader implications of external factors on cultural expression, highlighting the ongoing challenge of balancing heritage preservation with the acceptance of change.